2009
DOI: 10.1152/ajpheart.01141.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of integrin αVβ3prevents urokinase plasminogen activator-mediated impairment of cerebrovasodilation after cerebral hypoxia/ischemia

Abstract: Kiessling JW, Cines DB, Higazi AA, Armstead WM. Inhibition of integrin ␣V␤3 prevents urokinase plasminogen activator-mediated impairment of cerebrovasodilation after cerebral hypoxia/ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…We have previously shown that uPA binds directly to ␣ V ␤ 3 (17,24) and that plasminogen activators can promote the formation of a signal-transducing complex between low-density lipoprotein receptor and ␣ V ␤ 3 (1). The results of a more recent study extend these initial observations and indicate that uPA released after cerebral H/I impairs pial artery dilation induced by hypercapnia and hypotension through an integrin ␣ V ␤ 3 -dependent process (14). However, other as yet undefined mechanisms, which may include the opioid nociceptin/orphanin FQ and/or the activation of the N-methyl-D-aspartate receptor (2), may also contribute to the cerebrovascular derangement following cerebral H/I.…”
Section: Discussionsupporting
confidence: 71%
“…We have previously shown that uPA binds directly to ␣ V ␤ 3 (17,24) and that plasminogen activators can promote the formation of a signal-transducing complex between low-density lipoprotein receptor and ␣ V ␤ 3 (1). The results of a more recent study extend these initial observations and indicate that uPA released after cerebral H/I impairs pial artery dilation induced by hypercapnia and hypotension through an integrin ␣ V ␤ 3 -dependent process (14). However, other as yet undefined mechanisms, which may include the opioid nociceptin/orphanin FQ and/or the activation of the N-methyl-D-aspartate receptor (2), may also contribute to the cerebrovascular derangement following cerebral H/I.…”
Section: Discussionsupporting
confidence: 71%
“…Moving to large animal studies, Kiessling et al ( 33 ) described that inhibition of uPA could prevent vasodilatation, suggesting new therapeutic possibilities for clinical practice. On top of that, three other studies ( 36 , 37 , 39 ) described the effects of nociceptin/orphanin FQ and of Protein Tyrosine Kinase, showing that both can partially prevent hypotensive pial dilation impairment, when coadministred with the NMDA antagonist MK801.…”
Section: Resultsmentioning
confidence: 99%
“…tPA and uPA signaling mediation by integrin α v β 3 may also influence cerebrovascular tone through inhibition of important vasodilator stimuli such as autoregulation during hypotension and hypercapnia following global cerebral hypoxia/ischemia (Armstead et al. 2005b; Kiessling et al. 2009a).…”
Section: Tpa‐mediated Signaling Cerebral Hemodynamics and Outcome Amentioning
confidence: 99%
“…The effect of tPA on vascular tone may result from direct interaction with vascular smooth muscle cells to which it signals via the integrin a v b 3 to elicit vasoconstriction in a non-proteolytic manner . tPA and uPA signaling mediation by integrin a v b 3 may also influence cerebrovascular tone through inhibition of important vasodilator stimuli such as autoregulation during hypotension and hypercapnia following global cerebral hypoxia/ischemia (Armstead et al 2005b;Kiessling et al 2009a). Signaling is terminated through binding of PAI-1 by tPA, internalization of the integrin-tPA-PAI-1 ternary complex via LRPmediated endocytosis and dissociation of tPA-PAI-1 from the integrin .…”
Section: Tpa-mediated Signaling Cerebral Hemodynamics and Outcome Amentioning
confidence: 99%